Assessing Thermal Comfort Parameters in Public School Buildings for Tropical Areas: A Study of Teacher’s Lounge of SDN 27 in North Pontianak - Monica, Candra; Purnomo, Yudi; Zain, Zairin (International Journal of Environment, Architecture, and Societies, 2024)
The thermal comfort of the teacher’s lounge at the Public School Buildings of SDN 27 in North Pontianak is an important factor in providing room conditions to support the activities of teaching staff. Thermally, comfortable conditions play a role in increasing the productivity of teaching staff. However, the thermal condition of the teacher’s lounge at SDN 27 in Northest Pontianak does not meet the thermal comfort standards. Based on the facts, the thermal condition needs to be solved to achieve comforts in teacher’s lounge. Formulation of indicators for thermal comfort conditions was conducted in this research with CFD simulation. A seven-day research process obtained on the observation of thermal comfort levels in the teacher’s lounge. The modeling of the software includes indicators for adding heat loads under the roof and changing the wall paint color to beige. Both indicators can reduce the room temperature by 9.4 °C. In addition, changing the opening and applying cross ventilation are also indicators that the teacher’s lounge achieves a comfortable, thermally neutral condition. The final result of this study is that a teacher’s lounge has a 0.26 value of thermal comfort, and the room conditions have a neutral thermal sensation value.